EFEKTIVITAS PENERAPAN SMART MOBILITY DI KOTA BOGOR BERDASARKAN PERSEPSI MASYARAKAT - Adikarya, Dwi Utomo; Tanjung, Adinda Sekar (Jurnal Perencanaan dan Pengembangan Kebijakan, 2024)
Bogor City in collaboration with the United Station Development Program (UNDP) in 2017 with the Ministry of Communication and Information RI was appointed as an urban pilot project for the implementation of smart city as one of the solutions to solve urban problems. One of the smart city dimensions implemented in Bogor City is smart mobility. Smart mobility in Bogor City is certainly applied based on the issues and problems that exist in Bogor City such as congestion due to the volume of vehicles, limited area, limited road infrastructure, weakness of sidewalk and pedestrian infrastructure, and the high urbanization sector. Certainly smart mobility, which is used as one of the solutions in structuring transportation in a city, needs to be studied regarding its application to the community, whether its implementation in the community has gone according to its objectives. This study aims to assess the effectiveness of smart mobility implementation based on community perceptions through scoring analysis and descriptive analysis of 4 main variables, namely: integrated and multi-access transportation modes, non-motorized mobility, infrastructure technology that supports mobility, and security and safety in public spaces and public transportation. Through the research results, it is found that Bogor City has implemented the concept of smart mobility with 4 main variables resulting in a fairly effective score, around 80% of its smart mobility indicators have been implemented but need to be further optimized so that all sub-districts in Bogor City can feel the effectiveness of smart mobility.